Western Thrace as a border region in the light of geopolitical and population changes after World War I (1919–1928) - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2024)
The aim of the article is to show the borderlandness of the region called Western Thrace using the aspect od demographic and socio-political changes that occurred there after the First World War. Until the beginning of the 20th century this area was inhabited by communities with diverse cultural characteristics. Under Ottoman rule it was the part of a historical-geographical region called Thrace. It began to be recognised as a separate territorial unit and geopolitical question from the time of the Balkan Wars (Bulgarian Aegean Thrace, Turkish and Greek Western Thrace). It was finally annexed to Greece in 1920. On the basis of documentation from representatives of the Entente military, the League of Nations and the Greek authorities, the processes that contributed to the consolidation of a contemporary dichotomous cultural landscape in the region will be presented. On the one hand, it was subordinated to the paradigm of a unitary nation-state, while on the other hand, religious autonomy for more than a hundred thousand Muslims was included. In practice, however, this solution contributed to the isolation (ghettoisation) of the Muslim minority community, slowed down the integration of Muslims into Greek society and strengthened the control of the central administration over the affairs of the region.